Nivolumab drug holiday in patients treated for metastatic renal cell carcinoma: A real-world, single-centre experience - Bimbatti, Davide; Dionese, Michele; Lai, Eleonora; Cavasin, Nicolò; Basso, Umberto; Mattana, Alvise; Pierantoni, Francesco; Zagonel, Vittorina; Maruzzo, Marco (Frontiers in Oncology, 2022)
Introduction. Immunotherapy with nivolumab (a monoclonal antibody that targets the programmed cell death protein 1, PD1) has become the standard treatment for patients with metastatic renal cell carcinoma (mRCC) after progression to single-agent tyrosine kinase inhibitors. However, the optimal duration of immunotherapy in this setting has not yet been established. Patients and methods. We retrospectively reviewed all patients treated with nivolumab at our institution from January 2014 to December 2021 and identified those who discontinued treatment for reasons other than disease progression (PD). We then associated progression-free survival (PFS) and overall survival following treatment cessation with baseline clinical data. Results. Fourteen patients were found to have discontinued treatment. Four patients (28.6%) ceased treatment due to G3/G4 toxicities, whereas the remaining ten (71.4%) opted to discontinue treatment in agreement with their referring clinicians. The median duration of the initial treatment with nivolumab was 21.7 months (7.5-37.3); during treatment, two patients (14.3%) achieved stable disease as the best response, and the remaining twelve (85.7%) a partial response. At a median follow-up time of 24.2 months after treatment discontinuation, 7 patients (50%) were still progression-free. The median PFS from the date of discontinuation was 19.8 months (15.2 - not reached); a radiological objective response according to RECIST and treatment duration of more than 12 months were associated with a longer PFS. Three patients were re-treated with Nivolumab after disease progression, all of whom achieved subsequent radiological stability. Conclusion. In our experience, the majority of patients who discontinued treatment in the absence of PD were still progression-free more than 18 months after discontinuation. Patients whose initial treatment duration was less than 12 months or who did not achieve a radiological objective response had a greater risk of progression. Immunotherapy rechallenge is safe and seems capable of achieving disease control.